Transplantation of Hematopoietic Stem Cells Promotes Functional Improvement Associated with NT-3-MEK-1 Activation in Spinal Cord-Transected Rats - Xiong, Liu-Lin; Liu, Fei; Deng, Shi-Kang; Liu, Jia; Dan, Qi-Qin; Zhang, Piao; Zou, Yu; Xia, Qing-Jie; Wang, Ting-Hua (Frontiers in Cellular Neuroscience, 2017)
Transected spinal cord injury (SCT) is a devastating clinical disease that strongly affects a patient’s daily life and remains a great challenge for clinicians. Stem-cell therapy has been proposed as a potential therapeutic modality for SCT. To investigate the effects of hematopoietic stem cells (HSCs) on the recovery of structure and function in SCT rats and to explore the mechanisms associated with recovery, 57 adult Sprague-Dawley rats were randomly divided into sham (n = 15), SCT (n = 24), and HSC transplantation groups (n = 15). HSCs (passage 3) labeled by Hoechst 33342, were transplanted intraspinally into the rostral, scar and caudal sites of the transected lesion at 14 days post-operation. Both in vitro and in vivo, HSCs exhibited a capacity for cell proliferation and differentiation. Following HSC transplantation, the animals’ Basso, Beattie, and Bresnahan (BBB). locomotion scale scores increased significantly between weeks 4 and 24 post-SCT, which corresponded to an increased number of 5-hydroxytryptamine (5-HT) fibers and oligodendrocytes. The amount of astrogliosis indicated by immunohistochemical staining, was markedly decreased. Moreover, the decreased expression of neurotrophin- 3 (NT-3) and mitogen-activated protein kinase kinase-1 (MEK-1) after SCT was effectively restored by HSC transplantation. The data from the current study indicate that intraspinally administered HSCs in the chronic phase of SCT results in an improvement in neurological function. Further, the results indicate that intraspinally administered HSCs benefit the underlying mechanisms involved in the enhancement of 5-HT-positive fibers and oligogenesis, the suppression of excessive astrogliosis and the upregulation of NT3-regulated MEK-1 activation in the spinal cord. These crucial findings reveal not only the mechanism of cell therapy, but may also contribute to a novel therapeutic target for the treatment of spinal cord injury (SCI).